How (Not) to Elide Negation. (23rd January 2017) - van Craenenbroeck, Jeroen; Temmerman, Tanja
Abstract: This paper examines the behavior of English negative indefinites under VP ellipsis. The main empirical observation is that negative indefinites cannot take scope out of a verbal ellipsis site. We propose that negative indefinites involve fusion under adjacency between the clausal polarity head and an indefinite determiner and that this adjacency comes about under multidominance. Multidominance can feed the morphological coalescence of two syntactic terminals that on the surface do not appear to be linearly adjacent. The claim that there is a morphological relation between these two heads—rather than a syntactic one—is supported by the fact that it can be bled by ellipsis. Given that ellipsis is a process at Phonological Form (PF), it can block fusion, thus preventing high scope of negative indefinites out of an ellipsis site.